Lung cancer: analysis of biomarkers and methods of diagnostic and prognostic value - Yadav, S.; Agrawal, S.; Divya Ravali, S. S.; Pandey, A. (Cellular and Molecular Biology, 2017)
This paper summarizes the overwhelming evidence that targeted therapy is better than chemotherapy for the treatment of lung cancer. The focus is on lung cancer because of the sheer magnitude of this disease especially in males. In India, lung cancer constitutes 6.9 per cent of all new cancer cases and 9.3 per cent of all cancer related deaths in both sexes (1). Currently the world we reside has a norm of developing cure to an abnormal state of living body (so called disease) based on evidences, recognized during the diagnosis of the disease. It is done to ensure optimized therapy of treatment and maximize the outcome. Personalized medicine is also an uprising norm. In this kind, all the variables such as host, environment, patient, etc. are considered for an individual case and the course of treatment is followed based on the standard options available. Its main objective is the best interest of the patient. Through a survey conducted in the northern belt of the country we tried to determine the biomarkers currently being used and the scope of targeted therapy. Thus, in its most basic form medicine is not only a science but is also an art.